La comprensión de los textos como una experiencia reflexiva: Dos propuestas para la didáctica de la lengua - Sánchez Miguel, Emilio (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2024)
This work analyses the difficulties created by the comprehension of texts in order to give rise to "consideration of grammar". In this sense it is argued that comprehension is an immediate and an abstruse experience, and for this very same reason, rather unsuitable for the consideration of grammar. As a result two ways of making the comprehension process "visible" are expounded, both of which help to awaken awareness of the properties of texts and of the means of acting upon them.